Light the world and change its color: A case study in Italian secondary school using IBSE methodology. (August 2019) - Adesso, M G; Capone, R; Del Sorbo, M R; Fiore, O
Abstract: What color is it? It is not a trivial question: answer depends on the lamp used to light the world! Let's fix a light and measure with our human instruments, eyes and ears, a colored and orchestral environment: may we distinguish, at the same time, all the colors and sounds? Here we show a case study using Inquiry Based Science Education (IBSE), a teaching methodology, focused on the wave-matter interaction in daily experience and some ways to detect it by our senses. IBSE methodology engages students eliciting investigation of physical phenomena. General expected outcomes are an improvement of students' motivation and a more successful learning experience. We planned an educational path, based on investigation, for students attending the first year of high school. The course has been developed in four lessons (2.5 hours each) for a total of 10 hours. This path has been experimented in four different parallel classes. In each class, students have been divided into 5 or 6 groups. The first phase, "engage", is a simple trick: try to guess the color of four cards lighted with a monochromatic beam, red, blue, or green, in the dark. Once a white light is turned on, students will be surprised to see the true colors of the cards. After this "engagement", students "explore" interaction between wave and matter, accomplishing some tasks and trying to "explain" the observed phenomena. The third and most important step is to "extend": students directly experience additive color synthesis, with attention to pointillism, to subtractive color synthesis, and to superposition of sound. Later, each group, as in a flipped lesson, looks for answers to preliminary questions, by investigation: ear and eye behaviour, differences between electromagnetic and sound waves, electromagnetic spectrum. ICT is a valuable support in this phase. A multimedia product is requested at the end of investigation. In order to "evaluate" this educational path, it has been proposed to think about the use of a monochromatic lamp to change a colored word in another one, without some yellow and red letters. A feedback questionnaire has been also used to evaluate the educational path. The results of the questionnaire show that students are satisfied with this new methodology and activities. Satisfactory results, however, depend upon teacher's ability to motivate all students in attending classes.